The Influence of Organizational Culture on Organizational Attractiveness: Organizational Reputation as a Mediator - Suci Adriani, Allfatiana; Handoyo, Seger (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Organizational attractiveness is an important factor in companies' efforts to recruit and retain talent, especially in the midst of increasingly competitive labor competition. A positive organizational culture is believed to be able to improve prospective employees' perceptions of the organization, but its impact can vary depending on how the culture is perceived externally through the company's reputation. This study aims to determine the effect of organizational culture on organizational attractiveness, with organizational reputation as a mediating variable. The approach used is quantitative, with data collection techniques in the form of online surveys. The instruments used include the organizational attractiveness scale, culture organization scale and corporate reputation scale. Respondents in this study were 169 employees from various companies in Jombang Regency, East Java, with a minimum of three months of work experience. The data analysis technique used was model 4 analysis through PROCESS Macro SPSS from Hayes. The results of the study showed that organizational culture did not have a significant direct effect on organizational attractiveness. However, organizational culture has a positive and significant effect on organizational reputation, and this reputation significantly affects organizational attractiveness. Organizational reputation is proven to fully mediate the relationship between organizational culture and organizational attractiveness.